Pyometra and mammary gland tumor in a Beagle dog at the Veterinary Teaching Hospital of Brawijaya University, Malang, Indonesia - Nofan Rickyawan; Dian Vidiastuti; Karlina Karlina; Shelly Kusumarini (Ovozoa: Journal of Animal Reproduction, 2023)
A 12-year-old Beagle dog weighing 7.7 kg was brought to the Brawijaya University Veterinary Teaching Hospital in a state of dehydration, lethargy, and jaundice. On the 2nd day of hospitalization, the dog had mucopurulent discharge from the vagina. From the results of a complete blood count and ultrasonography (USG), the patient was diagnosed with pyometra and was treated with an ovariohysterectomy. After surgery the dogs was given cefotaxime 10 mg/kg bw, meloxicam 0.2 mg/kg bw, 0.9 ml vitamin K, and supportive therapy with Biodin® 0.5 mL and Modivitasan® 0.5 mL. Pyometra infection causes progesterone levels to rise, thereby triggering mammary gland tumor. On the 23rd day of hospitalization, a lump was found in the mammary gland. Fine needle aspiration (FNA) results showed the presence of Mott cells. The mammary gland tumor was treated with a single mastectomy. Mastectomy was performed when the dog was in stable condition, about a month after the ovariohysterectomy. Ovariohysterectomy and mastectomy were not performed simultaneously due to consideration of the patient's clinical condition, which made it impossible to get prolonged exposure to anesthesia. Post-mastectomy surgery the dogs were given cefixime 10 mg/kg bw, the analgesic meloxicam 0.2 mg/kg BW, and Biodin® 0.5 ml as supportive therapy. The postoperative wound healed well without complications. The patient recovered after one month of treatment.